Oliy pedagogika o‘quv yurtlarida astronomiya fanidan «quyosh» mavzusini o‘qitishda ilmiy- ijodiy yondashuv (SCIENCE and SOCIETY, 2022)
This article provides guidelines for studying the topic "Scientific and creative approach to the study of the topic of the Sun in astron- omy in higher pedagogical educational institutions." The given guidelines serve to increase the astronomical knowledge of pupils and students. Also, the developed guidelines have a special place in the study of astronomy in interdisplinary character